Pengabdian Kepada Masyarakat Melalui Kegiatan Cegah dan Tangani Stunting Untuk Meningkatkan Kesehatan Anak di Desa Eka Mulya (Mesuji Timur) - Erfha Nurrahmawati; Linda Agustina Saputri; Della Nur Rohmah; Riza Hersa Alfarizal; Muhammad Daffa Nurmalik; Mita Utami; Herani Ameliana Irawan; Elma Elma; Annisa Sofha Septiani (Masyarakat Berkarya : Jurnal Pengabdian dan Perubahan Sosial, 2024)
Stunting is a chronic nutritional problem that has a serious impact on children's physical and cognitive development, especially in developing countries like Indonesia. This condition is caused by various factors, including poverty, lack of access to nutritious food, poor sanitation, and minimal public knowledge about nutrition and health. Intervention in Eka Mulya Village, East Mesuji District, through socialization activities for preventing and handling stunting has succeeded in increasing public understanding and awareness of the importance of balanced nutrition and good health practices. This program has shown positive results in reducing stunting rates, however, challenges in the sustainability of education programs and monitoring the implementation of health practices still need to be addressed. Therefore, strong commitment and cooperation is needed from all parties to ensure the sustainability of this program and create a significant long-term impact in efforts to improve the quality of human resources and development in the future.